PENGATURAN KEIMIGRASIAN TENTANG VISA DAN IZIN TINGGAL BAGI DIGITAL NOMAD DI BALI - Tresnawan, I Made Pieri Rayana; Julianti, lis (Jurnal Hukum Mahasiswa, 2024)
Digital nomads are developing rapidly in Bali, this rapid development has not been able to be monitored optimally and effectively. The large number of Digital nomad tourists who enter using only visit visas is considered to be very detrimental in terms of foreign exchange income for the country. Research into the arrangements for Digital nomad visas and residence permits in Bali must be carried out with the aim of discussing the lack of clarity in the regulations governing this matter. This research discusses the regulation of visas and residence permits for foreign citizens in Indonesia and the legal consequences of the lack of regulations related to their regulation. The results of this research are that many foreigner take advantage of this regulatory vacuum which causes misuse of visas and residence permits for foreigner in Indonesia.